(untitled) (Innovative professional education, 2022)
The article considers the problem of modeling and measuring theprofessional value orientations of software applicants; substantiation of the pragmaticmethodology of metric measurement of the level of PR as a professional standard ofthe corresponding qualification, which is sufficient to fulfill the tasks of the relevantactual professional activity according to its quality standard